Changes of Electrocardiogram and Myocardial Enzymes in Patients with Intracerebral Hemorrhage. (1st February 2022) - Qin, Guannan; Dai, Chuanyang; Feng, Shuang; Wu, Guofeng
Abstract : Purpose . Cardiac complications are common in patients with spontaneous intracerebral hemorrhage (ICH). The present study is aimed at observing the incidence of cardiac complications after ICH, so as at improving the understanding of the relationship between cardiac complications and ICH. Methods . This is a retrospective study on analyzing electrocardiogram (ECG) and serum myocardial enzyme of 208 patients with ICH admitted to a tertiary hospital from 2018 to 2019. For each patient, demographics, medical history, clinical presentation, ECG, serum myocardial enzyme, and head CT on admission were reviewed. Mortality was noted. Results . Among the 208 patients, 145 (69.71%) had one or more ECG abnormalities. The top three abnormalities were corrected QT interval (QTc) prolongation 52 (25%), ST depression 48 (23.08%), and T wave inversion 38 (18.27%). One hundred and thirty-nine patients (66.83%) had increased serum levels of at least one kind of myocardial enzyme, which were high-sensitive cardiac troponin T (hs-cTnT) 79 (37.98%), lactic dehydrogenase (LDH) 80 (38.46%), creatine kinase (CK) 57 (27.40%), and creatine kinase-myocardial subfraction (CKMB) 57 (27.40%). The logistic regression analysis showed the following: secondary intraventricular hemorrhage (SIVH) (odds ratio (OR) 5.32; 95% confidence interval (CI) 2.55–11.08; p < 0.001 ) and hematoma volume > 30 ml (OR 3.81; 95% CI 1.86–7.81; p < 0.001 ) were independent predictive factors of QTc prolongation; thalamus location (OR 5.79; 95% CI 1.94–17.28; p < 0.05 ), hematoma volume > 30 ml (OR 24.187; 95% CI 3.14-186.33; p < 0.05 ), insular involvement (OR 19.08; 95% CI 5.77-63.07; p < 0.001 ), and SIVH (OR 2.62; 95% CI 1.69-5.86; p < 0.05 ) were independent predictive factors of ST depression; insular involvement (OR 2.90; 95% CI 1.12–7.50; p < 0.05 ) and hematoma volume > 30 ml (OR 1.98; 95% CI 1.06–3.70; p < 0.05 ) were independent predictive factors of increase of CK; Glasgow Coma Scale (GCS) (OR 0.86; 95% CI 0.78–0.98; p < 0.05 ) and insular involvement (OR 5.56; 95% CI 1.98–15.62; p < 0.05 ) were independent predictive factors of increase of CKMB; SIVH (OR 2.05; 95% CI 1.07–3.92; p < 0.05 ) was independent predictive factor of increase of LDH; age (OR 1.03; 95% CI 1.01–1.06; p < 0.05 ), blood glucose on admission (OR 1.10; 95% CI 1.01–1.20; p < 0.05 ), and history of antiplatelet drug use (OR 3.50; 95% CI 1.01–12.12; p < 0.05 ) were independent predictive factors of hs-cTnT. All the injury indexes were not related to in-hospital mortality. Conclusion . The study suggests that insular involvement, hematoma volume > 30 ml, and SIVH are the strongest risk factors for ECG abnormalities and elevated myocardial enzymes after ICH followed which are the risk factors such as GCS, age, admission blood glucose, and ICH location in the thalamus.